Syntheses, Solid State Structures and Photochemistry of α,ω-Bis-[(1,8-dichloroanthracen-10-yl)dimethylsilyl]alkanes - Niermeier, Philipp; Lamm, Jan-Hendrik; Linnemannstöns, Marvin; Neumann, Beate; Stammler, Hans-Georg; Mitzel, Norbert W. (Synthesis, 2018)
Starting from 10-bromo-1,8-dichloroanthracene, a series of 1,8-dichlorinated anthracene derivatives, flexibly bridged in position 10 by –Me2Si– and –Me2Si–(CH2)n–SiMe2– linker units, were synthesised. The linked anthracenes were generated by converting (1,8-dichloroanthracen-10-yl)lithium with chlorosilanes in salt-elimination reactions. The bichromophors were tested in UV light induced photo reactions. None of the new compounds yielded any intra- or intermolecular photoproduct. All α,ω-(dimethylsilyl)alkane-linked bisanthracenes decomposed to give 1,8-dichloro-9-hydroxyanthracen-10(9H)-one in the presence of oxygen. A completely different behaviour was shown by the bisanthracenyldimethylsilane, undergoing a 9,10:3′,4′-photocyclomerisation reaction. The new compounds were characterised by NMR spectroscopy, mass spectrometry and in most cases by X-ray diffraction studies.
Keywords: anthracenes; salt metathesis reactions; solid-state structures; photocyclomerisation; oxygenation